Application of Islamic Spiritual Intelligence as a MSMe Strategy in Post-Pandemic - Arief Dwi Saputra; Alfina Rahmatia; Andi Azhar (International Journal of Islamic Business and Economics (IJIBEC), 2022)
This study aims to investigate how Islamic spiritual intelligence is applied as a strategy for entrepreneurship in facing the post-pandemic. This study used a qualitative research strategy with a sample of 128 respondents. The root of the problem is reviewed from the literature review and strengthened by collecting data from the in-depth interview process. The data is processed using the Nvivo 12 application with coding similarity analysis then the results of the study are used as a reference and conclusions through the data obtained. The results of this study found that there are seven elements of spiritual intelligence from an Islamic perspective, namely faith, piety, morality, shiddîq (honest), amânah (responsible), tablîgh (conveying), fathânah (intelligent), discipline, visionary, and empathy. A review of the total percentage of 100% has the potential for Islamic entrepreneurship in achieving business sustainability in the ability of business actors to manage their business through attitudes and decision-making that rely on elements of Islamic spirituality intelligence.